Conditional deletion of TRPC1 channel modulates synaptic plasticity, long term depression, and memory extinction in Fragile X syndrome mice - Farah Issa; Xavier Yerna; Thibaud Parpaite; Caren Jabbour; Olivier Schakman; Nicolas Tajeddine; Roberta Gualdani; Philippe Gailly (iScience)
Summary: Group I metabotropic glutamate receptors (mGluRs), particularly mGluR5, regulate synaptic plasticity via long-term depression (mGluR-LTD), a process implicated in declarative memory. We previously identified TRPC1, a highly expressed hippocampal ion channel, as a key mGluR5 effector. Using a Cre-tamoxifen system, we acutely deleted Trpc1 in a Fragile X syndrome (FXS) mouse model, characterized by mGluR5 hyperactivity, enhanced mGluR-LTD, and social deficits. In FXS neurons, mGluR5-evoked currents were elevated and normalized by Trpc1 deletion. This deletion also improved social behavior and reduced anxiety. Notably, it abolished mGluR-LTD and normalized memory extinction, as shown in behavioral assays. Mechanistically, mGluR5 activation induced ARC protein expression via eEF2K- and ERK1/2-dependent pathways, modulating Arc translation and transcription. These findings highlight TRPC1 as a crucial mediator of pathological plasticity in FXS and a potential therapeutic target.